Needs Analysis for Developing Culturally Responsive Narrative Reading Materials for Junior High School EFL Learners - Wineka Satya; Rita Inderawati; Sary Silvhiany (VELES Voices of English Language Education Society, 2025)
This study examines the needs of junior high school students for developing English narrative reading materials that integrate local culture, drawing on perspectives from both learners and teachers. Data were collected through questionnaires and semi-structured interviews and analysed using a combination of quantitative and qualitative approaches. The findings indicate that students perceive English as necessary to support their academic development and future opportunities, yet most demonstrate only basic proficiency. Students reported difficulties understanding narrative texts, particularly with vocabulary, identifying main ideas, and organising events. Narrative text emerged as the most frequently requested genre, and students preferred multiple-choice and short-essay assessments. The study also found a strong need for materials that reflect students’ learning contexts, as they possess limited knowledge of local cultural heritage and currently have no access to English reading materials that incorporate local culture. Both students and teachers emphasised that integrating local cultural content, especially folklore, would not only strengthen language competence but also enhance motivation and cultural awareness. Based on these findings, the development of supplementary narrative reading materials grounded in local culture is recommended to ensure alignment with students’ proficiency levels, address reading comprehension challenges, and foster meaningful, culturally responsive learning experiences.